PP.02.14: SOCIAL DEPRIVATION AND CARDIOVASCULAR RISK ASSESSMENT IN FRENCH POPULATION. (June 2015) - Tartiere, J.-H.; Brucker, M.; Babici, D.; Steichen, O.; Krummel, T.; Sosner, P.; Ott, J.; Le Coz, S.; Rosenbaum, D.; Dourmap, C.; Dimitrov, Y.; Iaria, P.; et al.
Abstract : Objective: Cardiovascular prevention and management of hypertension is mainly based on the detection and treatment of metabolic usual risk factors or dietary improvement. This approach has difficulty in assessing the risk of disadvantaged populations where social deprivation seems to play a major role. Design and method: 263 consecutives hypertensive patients were refered to specialists and assessed for social deprivation through the EPICES questionnaire as for usual risk factors and several socio-economic data. Results: Patients were 63 ± 13 years old and 59% were men. Risk factors were diabetes (39%), dyslipidemia (68%), active smoking (32%). Alcoholic consumption of more than once per week was present in 28%, a physical activity for at least once a week in 30%. Systolic, diastolic and pulse pressure were 143 ± 21, 81 ± 13 and 63 ± 18 mmHg. The mean number of antihypertensive drugs was 2.8 ± 1.3. A target organ damage was frequent, including peripheral vascular disease (18% lower limbs, 15% supra aortic trunks, 5% abdominal aorta, 9% stroke/TIA), coronary heart disease (19%), heart failure (8%) and left ventricular hypertrophy (30%). EPICES score over 30, associated with a high level of social deprivation, was present in 27% of the population. The survey showed that 76% of patients had a social insurance for long duration disease, 22% lived in a city of more than 50, 000 inhabitants, 35% had at least bachelor level, 59% were retired and the mean number of intervening medical, paramedical and social workers was 2.3 ± 0.8 per patient. Social deprivation was independently associated with the lack of insurance for long duration disease, a high pulse pressure and city of over 50, 000 inhabitants. Conclusions: In this hypertensive population a third of patients may be regarded as living in social deprivation. This condition is most often associated with an urban population and low social support of their disease. These patients also have an increased arterial stiffness despite no difference in other cardiovascular risk factors.